Genetic strain differences in platelet aggregation and thrombus formation of laboratory rats - Sudo, Toshiki; Ito, Hideki; Hayashi, Hideki; Nagamura, Yoshie; Toga, Kazuyuki; Yamada, Yoshihisa (Thrombosis and Haemostasis, 2007)
Rats are employed to investigate the role of platelets in thrombus formation under flow conditions in vivo and to evaluate the pre-clinical potential of antiplatelet drugs. While Wistar and Sprague-Dawley (SD) strains are commonly used in thrombosis models, a number of rat strains have been established. Each strain possesses genetically unique characteristics such as hypertension, hyperglycemia or hyperlipidemia. The appropriate selection of a strain might have advantages for physiological and pharmacological studies. Comparative investigation of platelet aggregation among laboratory strains of rats is useful for the development of thrombosis models. In the present study, platelet aggregation response in eight laboratory rat strains, ACI, Brown Norway (BN), Donryu, Fischer 344 (F344), LEW, SD, Wistar and WKAH, were compared. Considerable strain differences were observed in ADP-, collagen- and TRAP-induced platelet aggregation. SD and BN are high-platelet-aggregation strains, while F344 and ACI are low-response strains. In the arteriovenous shunt thrombosis model, SD formed larger thrombi than F344 andWistar rats. In the FeCl 3 -induced thrombosis model with the carotid artery, the time to occlusion of SD was significantly shorter than of F344 and ACI rats. F344 and ACI rats had significantly increased bleeding times compared with SD rat. The present study demonstrates that there are considerable strain differences in platelet aggregation among laboratory rats, which reflect thrombus formation.
Keywords: Platelet aggregation; rat; strain difference; thrombus formation